Abscission zone metabolism impacts pre- and post-harvest fruit quality: a very attaching story - Tranbarger, Timothy J.; Tadeo, Francisco R. (Frontiers in Plant Science, 2025)
The function of abscission zones (AZs) determines the timing of fleshy fruit abscission, with important consequences not only for the optimal fruit harvest, but also on the overall final fruit quality. In this context, chemical treatments are commonly used at different stages of fruit development to control fruit abscission, which can also have positive or negative effects on fruit quality. In the current review, we examine commonly used chemicals that affect the metabolic activity in the AZs of fleshy fruit, in addition to their effects on fruit quality characteristics. The main hormone metabolism and signaling in the AZ include that of ethylene, auxin, abscisic acid and jasmonates, and the molecular components that are involved are covered and discussed, in addition to how these hormones work together to regulate AZ activity and hence, affect fruit quality. We focus on studies that have provided new insight into possible protein complexes that function in the AZ, including multiple MADS-box transcription factors, with potential overlapping regulatory roles which exist between AZ development, ethylene production, AZ activation, fruit ripening and overall fruit quality. The view of the AZ as a cross roads where multiple pathways and signals are integrated is discussed.